Spindle cell carcinoma of the maxillary sinus with extension to the oral cavity - Donohue-Cornejo, Alejandro (2020)
Spindle cell carcinoma (SCC) is a rare variant of squamous cell carcinoma characterized by elongated and pleomorphic epithelial cells that resemble a sarcoma. Due to its rareness, and histological resemblance to various sarcomas, the diagnosis of this neoplasia is challenging. Herein we present the case of an 82-year-old female with a polypoid, ulcerated, soft tissue mass located on the left side of the maxilla. The tomographic examination showed a hyperdense mass that infiltrated the orbital cavity, ethmoidal cells, middle and lower nasal concha, maxillary sinus, zygomatic arch, and mandibular ramus on the left side. Histopathologically, the tumor was composed of spindle cells that were sarcomatous in appearance, with aberrant mitosis, along with a group of pleomorphic cells with a more epithelioid and hyperchromatic appearance on a stroma of densely vascularized fibrous tissue. The immunohistochemistry panel used to determine the lineage of the tumor rendered the diagnosis of SCC. The diagnosis of SCC is challenging to the pathologist since its morphology can resemble a sarcoma. Thus, immunohistochemistry is a valuable resource to support the diagnosis. We propose that SCC should be considered when examining a biphasic neoplasm with the aforementioned histological characteristics and markers.